Exciton–Polaron‐Induced Aggregation of Wide‐Bandgap Materials and its Implication on the Electroluminescence Stability of Phosphorescent Organic Light‐Emitting Devices. (29th January 2014) - Wang, Qi; Sun, Bin; Aziz, Hany
<x xml:space="preserve">Abstract</x> The degradation mechanisms of phosphorescent organic light‐emitting devices (PhOLEDs) are studied. The results show that PhOLED degradation is closely linked to interactions between excitons and positive polarons in the host material of the emitter layer (EML), which lead to its aggregation near the EML/electron transport layer (ETL) interface. This exciton–polaron‐induced aggregation (EPIA) is associated with the emergence of new emission bands at longer wavelengths in the electroluminescence spectra of these materials, which can be detected after prolonged device operation. Such EPIA processes are found to occur in a variety of wide‐bandgap materials commonly used as hosts in PhOLEDs and are correlated with device degradation. Quite notably, the extent of EPIA appears to correlate with the material's bandgap rather than with the glass‐transition temperature. The findings uncover a new degradation mechanism, caused by polaron‐exciton interactions, that appears to be behind the lower stability of OLEDs utilizing wide‐bandgap materials in general. The same degradation mechanism can be expected to be present in other organic optoelectronic devices.